Factors Related to HIV/AIDS Prevention Behavior Among Female Sex Workers in Padang in 2018 - Yuliza, Wilda Tri; Hardisman, Hardisman; Nursal, Dien Gusta Anggraini (Faculty of Medicine, Universitas Islam Sultan Agung (UNISSULA), Indonesia, 2019)
Background: HIV/AIDS has a huge risk transmitted through sexual intercourse with multiple partners, including Female from Sexual Workers and customers due to perform unsafe sexual behavior. The increasing prevalence of HIV/AIDS among female sex workers in Indonesia related to the health prevention behaviors were too low.Objective: To determine the factors related to the behavior of HIV/AIDS prevention at the FSW.Methods: This study uses a quantitative approach by the cross-sectional design. Researchers took a sample of 50 female sex workers in Padang using Consecutive Sampling method. Analysis of the data in this study using univariate, bivariate, and multivariate analyzes.Results: Results showed 66% of FSW have a good preventive behavior, there is a significant relationship between education (p= 0.024), knowledge (p= 0.002), attitude (p= 0.0001), specificity (p= 0.006), support fellow of FSW (p= 0.027), and support officers (p= 0.013) to conduct HIV/AIDS prevention at the FSW. Whereas the availability of condoms, access to information and support pimps have no meaningful relationship to the behavior of HIV/AIDS prevention. The most dominant factor related to the behavior of HIV/AIDS prevention is the attitude (OR= 82.877 CI: 7.717-89.079).Conclusion: Factors in themselves greatly influence the behavior of female sex workers in preventing HIV/AIDS coupled with the support of the closest people such as friends, pimps, and officers who make female sex workers feel comfortable and feel cared for. Â